Abū Ḥayyān’s Legal Exegesis of QS al-Nisāʾ [4]:1: A Study of Qirāʾāt Syādhah and the Principle of Egalitarian Creation - Romlah Widayati (QOF, 2025)
The interpretation of legal verses in the Qur’an has traditionally emphasized qirāʾāt mutawātirah, often overlooking qirāʾāt shādhah, which hold significant interpretive potential that has not been fully utilized in Islamic legal exegesis. This article examines Abū Ḥayyān al-Gharnāṭī’s interpretation of QS al-Nisāʾ [4]:1 through the analytical framework of qirāʾāt shādhah as the primary instrument of study. The research employs a descriptive-analytical methodology, using tafsīr al-Baḥr al-Muḥīṭ as the principal source, supplemented by critical engagement with other classical tafsīr works for contextualization. Findings indicate that Abū Ḥayyān critically rejects the traditional narrative of Ḥawwāʾ’s creation from Ādam’s rib, and by referencing qirāʾāt shādhah, he affirms the ontological equality of men and women, both created from the same substance. Furthermore, the verse is interpreted as an ethical directive to maintain familial relationships and social cohesion, integrating theological, linguistic, and moral dimensions. This study demonstrates how the diversity of qirāʾāt can enrich legal exegesis, offering inclusive and progressive perspectives, while creating space for alternative readings that support gender-equitable and contextually grounded understandings of Islamic law. It contributes to the broader discourse on Islamic legal hermeneutics and highlights the importance of integrating neglected recitations to advance ethical, gender-conscious, and contextually relevant interpretations